(untitled) (Research, Society and Development, 2021)
Objective: To identify the guides of assistance to the health of women with hypertensive syndrome in primary care. Method: This is an integrative literature review with the following guiding question: What are the health care guides for women with hypertensive syndrome in primary care? The PVO strategy was used. The population was composed of 4,518 studies, with five studies as sample. Results: There was a prevalence of guides derived from Brazilian institutions that sought to identify SHEG and define an action plan for morbidity. However, drug approaches prevailed over strategies to promote health and prevent diseases. Gestational hypertension, pre-eclampsia and eclampsia were identified as the main comorbidities with direct assistance provided by physicians and nurses. Conclusão: Destarte-se evidencia-se uma prática baseada apenas na identificação e referenciamento da mulher sem o acompanhamento adequado, tracingando-se as condutas apenas em fluxogramas. Furthermore, there is a need to promote evidence-based practice as a method to guide care in the care assistence.